PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA TANPA HAK MENDISTRIBUSIKAN GAMBAR PORNOGRAFI DISERTAI PEMERASAN: Conviction of Criminal Offenders Without The Right To Distribute Pornographic Images Accompanied by Extortion - Ahmad Muhajir; Vientje Ratna Multiwijaya (Universitas Trisakti, 2024)
Punishment of Perpetrators of Crimes Without the Right to Distribute Pornographic Images accompanied by Extortion with the study of decision number 619/Pid.Sus/2021/PN Jkt.Sel. The main issues are 1) How is the sentence of the judge in decision number 619/Pid.Sus/2021/PN Jkt.Sel appropriate or not based on Article 27 (4) jo. Article 45 (4) of electronic information and transaction law? 2) Are the criminal sanctions against the perpetrators in decision number 619/Pid.Sus/2021/PN Jkt.Sel in accordance with the purpose of punishment? This study uses a normative research type that is descriptive using secondary data which is analyzed qualitatively by drawing deductive conclusions. The conclusions of the study are 1) Judge conviction in decision number 619/Pid.Sus/2021/PN Jkt.Sel based on Article 27 (4) jo. Article 45 (4) of electronic information and transaction law is incorrect. 2) The criminal sanction against the perpetrator in decision number 619/Pid.Sus/2021/PN Jkt.Sel is not in accordance with the purpose of sentencing. The results of this study are related to legal facts and criminal purposes 3R and 1D, so the perpetrator should be subject to Article 27 (4) jo. Article 45 (4) of the electronic information and transaction law jo. Article 368 of the Criminal Code with 6 years in prison